2020
DOI: 10.33752/jfas.v1i2.176
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Working Capital Turnover dan Leverage Terhadap Financial Distress (Study Empiris pada Perusahaan Jasa SubSektor Property, Real Estate dan Kontruksi Bangunan yang Tercatat di Bursa Efek Indonesia)

Abstract: This study aims to determine whether or not the influence of Working Capital Turnover and Leverage to Financial Distress (Empirical Study on Service Company Sub Sector Property, Real Estate and Building Construction Listed on Indonesia Stock Exchange) during the period 2012-2017. Independent variable Working Capital Turnover using Net Working Capital Turnover and leverage using debt to assets ratio (DAR). The dependent variable of financial distress uses Z-Score Altman Modification. The research method used is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Working Capital dan Financial Distress Sebelumnya telah dilakukan penelitian untuk mencari tahu hubungan Working Capital dengan Financial distress, diantara lain: (Lestari & Ardiana, 2019) penelitiannya menemukan pengaruh positif dan signifikan antara Working Capital terhadap Financial Distress. Penelitian ini sejalan dengan penelitian (Desiyanti et al, 2019).…”
Section: Kaitan Antar Variabelunclassified
“…Working Capital dan Financial Distress Sebelumnya telah dilakukan penelitian untuk mencari tahu hubungan Working Capital dengan Financial distress, diantara lain: (Lestari & Ardiana, 2019) penelitiannya menemukan pengaruh positif dan signifikan antara Working Capital terhadap Financial Distress. Penelitian ini sejalan dengan penelitian (Desiyanti et al, 2019).…”
Section: Kaitan Antar Variabelunclassified
“…Zulaecha & Mulvitasari (2019) dan Lestari & Ardiana (2019) revealed that the use of debt harms financial difficulties in property, real estate, and building construction companies. The level of use of debt is one factor that can provide information about the company's health condition.…”
Section: G Property Real Estate and Building Constructionmentioning
confidence: 99%
“…The level of use of debt is one factor that can provide information about the company's health condition. The higher the use of debt, the more significant its financial burden (Lestari & Ardiana, 2019) is interest costs. A low level of debt usage impacts the loan interest rate to below so that the ability to generate profits from the use of debt is even greater.…”
Section: G Property Real Estate and Building Constructionmentioning
confidence: 99%
See 1 more Smart Citation